Structure-based dynamic analysis of the glycine cleavage system suggests key residues for control of a key reaction step - Han Zhang (Nature Portfolio, 2020)
Han Zhang et al. report molecular dynamics simulations and mutational analysis of a key process of the E. coli glycine cleavage system, an important enzyme complex in C1 metabolism. They identify a key amino acid residue controlling the release of the swinging aminomethyl lipoate arm and increase the overall reaction rate of glycine cleavage by more than twice, providing a strategy for manipulating this reaction system for use in synthetic biology.